Improving light output power of AlGaN-based deep-ultraviolet light-emitting diodes by optimizing the optical thickness of p-layers. (28th July 2021) - Matsukura, Yusuke; Inazu, Tetsuhiko; Pernot, Cyril; Shibata, Naoki; Kushimoto, Maki; Deki, Manato; Honda, Yoshio; Amano, Hiroshi
Abstract: In this study, we investigated the relationship of light output power with the optical thickness of the p-layers in AlGaN-based deep ultraviolet light-emitting diodes with a transparent high-Al-composition p-AlGaN clad layer, a thin p-GaN contact layer, and a reflective p-type electrode. By adjusting the thickness of the transparent high-Al-composition p-AlGaN clad layer, we observed a marked change in light output power. A maximum light output power of 385 mW at 1500 mA, a maximum external quantum efficiency of 15.7% at 10 mA, and a maximum wall-plug efficiency of 15.3% at 10 mA were obtained at an emission wavelength of 275 nm.